Utilization of Coconut Shell Activated Charcoal in Adsorbing Laundry Wastewater - Ade Damaria Mukti; Rani Yosilia; Eka Septiawati (WISE Pendidikan Indonesia, 2024)
Adsorption involves the attachment of molecules or ions onto the surface of an adsorbent. Activated charcoal is effective in adsorbing organic substances, odors, colors, and various pollutants from water. In this process, toxic particles adhere to the charcoal, reducing pollutant concentrations and improving water quality. This study examines the effectiveness of coconut shell activated charcoal in adsorbing laundry wastewater, specifically focusing on reducing BOD, COD, and coliform levels. A quantitative approach using a completely randomized design (CRD) was employed, with varying charcoal weights (1 g, 2 g, and 3 g) to assess its impact on water quality. Each treatment used 100 ml of laundry wastewater. The results showed that activated charcoal from coconut shells was effective in reducing BOD and COD levels, but not in lowering coliform concentrations. The third treatment (3 g) yielded the most significant BOD reduction, with a final concentration of 20 mg/L and an effectiveness of 96.66%. For COD, the third treatment resulted in a concentration of 71 mg/L and an effectiveness of 93.07%. However, coliform levels remained unchanged in all treatments, exceeding 160,000/100 mL, far above the standard maximum of 3000/100 mL, with 0% effectiveness in reducing coliform.